Usage of Media Advocacy Education by the Independent National Electoral Commission on Voters’ Turnout in Elections: A Study in Delta State, Nigeria - Akpoghiran, Idamah Patrick; Okoro, Ferdinand Eloke (NIU Journal of Social Sciences; Vol 7 No 3 (2021): KIU Journal of Social Sciences, Vol. 7 No. 3, September 2021, 2021)
The study examines how the Independent National Electoral Commission (INEC) in Nigeria use media advocacy as a way to educate the electorates on election turnout in Delta state, Nigeria in the 2019 elections. The main objective of the study was to ascertain how media advocacy was used by INEC for voters’ participation. The study was anchored on framing theory, which posits a social call for voters’ turnout and behaviour. In order to ascertain the objectives of the study, a sample of 63 participants or electorates from the three senatorial districts in Delta state were administered with a questionnaire. Data collected and analysed showed that though media advocacy was capable of making voters to participate in election but it does not determines voter’s behaviour during election. Media advocacy helped in voters’ turnout, however, the level of age, level of education and political party affiliation, regionalism, money politics and ethnic group were strong factors for voters’ turnout and behaviour during election. Consistent media advocacy education is required for voters’ turnout and proper conducts during elections.. Media advocacy education is needed to influence positive ideas on a voter. Keywords: Elections; Media advocacy education; Voters; Voters’ turnout; Voter’s behaviour